2021
DOI: 10.21614/sgo-26-2-279
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Nutritional/Inflammatory Scores as a Preoperative Predictor of Short-Term Surgical Risks in Hepatectomy for Colorectal Metastasis

Abstract: Background: Various nutritional/inflammatory scores reportedly correlate with surgical outcomes of abdominal surgery, while it remains inconclusive which one is the best in prediction of short-term surgical outcomes of patients with colorectal liver metastasis (CLM). Methods: Clinical records of 367 hepatectomies for 267 patients with CLM were retrospectively reviewed. Preoperative nutritional/inflammatory status was determined using 14 reported nutritional/inflammatory scores and predictive powers of these sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
1
1
Order By: Relevance
“…In the field of surgery, correlations between the preoperative CONUT score and the short-term/longterm outcomes have been reported for various cancers, while its true usefulness in patients with CRC remained controversial [17,18,26]. Unlike in the case of more invasive surgeries, such as for colorectal liver metastases or hepatocellular carcinoma [15,16], the preoperative nutritional status was not associated with the short-term surgical outcomes after colectomy in the present analysis either. However, the present analysis clearly demonstrated that sustained malnutrition after colectomy was independently associated with a higher risk of tumor recurrence and poorer survival outcomes.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…In the field of surgery, correlations between the preoperative CONUT score and the short-term/longterm outcomes have been reported for various cancers, while its true usefulness in patients with CRC remained controversial [17,18,26]. Unlike in the case of more invasive surgeries, such as for colorectal liver metastases or hepatocellular carcinoma [15,16], the preoperative nutritional status was not associated with the short-term surgical outcomes after colectomy in the present analysis either. However, the present analysis clearly demonstrated that sustained malnutrition after colectomy was independently associated with a higher risk of tumor recurrence and poorer survival outcomes.…”
Section: Discussioncontrasting
confidence: 62%
“…Recent reports have suggested that the preoperative inflammatory status and/or nutritional measures are predictive of the long-term outcomes in patients with CRC [9][10][11][12][13]. Our group has recently reported the prognostic significance of the Controlling Nutritional Status (CONUT) score [14] in patients with colorectal liver metastases or hepatocellular carcinoma [15,16]. However, there have been few studies on the prognostic value of the CONUT score in patients with CRC [17][18][19].…”
Section: Introductionmentioning
confidence: 99%